Ảnh hưởng của hơi nước đến hoạt tính của một số xúc tác oxit kim loại trong phản ứng oxi hóa hoàn toàn p-xylen - Lộc, Lưu Cẩm; Phúc Diễm, Nguyễn Thị; Thoảng, Hồ Sĩ (Vietnam Journal of Chemistry, 2014)
Physico-chemical characteristics and activity of mono- and poly-oxide catalyst, based on CuO, Cr2O3, MnO2, CeO2on γ- and α-Al2O3as carriers, have been studied. Interactions between active phases as well as interactions of active phases with carriers and promoting additive CeO2were characterized by BET, XRD and TPR methods. Activity of the catalysts was determined in complete oxidation of p-xylene at the temperature range 200 - 340oC in a flow of nitrogen, containing molecular oxygen and various concentrations of water steam. It has been found that all poly-oxide catalysts (CuO-Cr2O3, CuO-MnO2, CuO-MnO2-Cr2O3supported on γ- as well as α-Al2O3) expressed the highest activity; the catalysts containing single oxide indicated less activity, but an addition of CeO2improved their activity except for the catalyst of 15%MnO2/γ-Al2O3modified by 7% CeO2. In the presence of water steam, except for CuO, all mono-oxide catalysts indicated the less stability. Cr2O3has been found to be a stabilizing component in poly-oxide catalysts. The catalyst 5%MnO2+2%CeO2/α-Al2O3has been indicated as the most stable one in the presence of water steam. The activity as well as the stability of catalysts were discussed in the relation with their physico-chemical properties